Pencemaran Laut Oleh Limbah Plastik Di Selat Malaka: Tanggung Jawab Negara Pantai Dan Efektivitas Penegakan Hukum Berdasarkan Marpol 73/78 Dan Unclos 1982 - Vico Adela Joan Pratama; Kartika Dewi Lestari; Zahra Oktaviola; Muhammad Rafli Rafael Pratama (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The Strait of Malacca is one of the busiest international shipping lanes in the world, with more than 80,000 vessel transits annually. This condition makes the region vulnerable to transboundary marine pollution, particularly from plastic waste. Although Indonesia, Malaysia, and Singapore have ratified the MARPOL 73/78 Convention, whose Annex V generally prohibits the disposal of plastics at sea, practical enforcement remains challenging. This study aims to examine the legal obligations of the three coastal states under MARPOL 73/78 within the framework of UNCLOS 1982, assess the comparative effectiveness of implementation, and formulate policy recommendations. The study employs normative legal research using statute and comparative approaches. The findings indicate a significant gap between international legal commitments and practical enforcement. Among the three states, Singapore demonstrates relatively stronger enforcement capacity, while Malaysia occupies an intermediate position and Indonesia faces more complex implementation challenges. The study concludes that stronger regional coordination, harmonisation of domestic regulations, and the establishment of a joint monitoring mechanism are essential to improve marine environmental protection in the Strait of Malacca.